Frame Spillover: Media Framing and Public Opinion of a Multifaceted LGBT Rights Agenda. Issue 2 (7th September 2012) - Engel, Stephen M.
<x xml:space="preserve">Abstract</x> Between May and July 2003, a shift in how the US public viewed the legality of consensual homosexual sex occurred. While in May the largest percentage of respondents to date supported decriminalizing such activity, that percentage dropped eleven points two months later. Similar declines in support were evident in the same period over a range of gay and lesbian rights claims. The ruling in Lawrence v. Texas (2003) decriminalizing homosexual sex is the obvious intervening event. To explain this pattern, coding of print and televised news coverage of the ruling throughout 2003 was undertaken. Coverage was not overtly negative in terms of antigay rhetoric or hostility toward the judiciary; rather, the dominant media frame focused on the implications of Lawrence for an entirely separate rights issue: marriage equality. This article examines the dynamic of frame "spillover, " or the idea that media focus on a distinct and not widely supported rights claim in a multifaceted rights agenda might depress support across the entire rights agenda. The findings call for further research, and they have implications for scholarship on public opinion, social movement framing, and ideational development and policy debate as studied within the broader field of American political development.